INVESTIGAÇÃO DAS PROPRIEDADES FUNCIONAIS DE UM NOVO COMPOSTO DE COORDENAÇÃO LAUSONATO - GA (III) - Pinheiro, A. C. N.; Teixeira, E. I.; da Cruz, M. M.; Gonçalves, A.; Faganello, N. L.; dos Anjo, A. (ANAIS DO ENIC, 2017)
-